The text of the New Testament in contemporary research: essays on the status quaestionis - Ehrman, Bart D.; Holmes, Michael W. (New testament tools, studies and documents, 2013)
Preliminary Material /Bart D. Ehrman and Michael W. Holmes -- The Papyrus Manuscripts of the New Testament /Eldon Jay Epp -- The Majuscule Manuscripts of the New Testament /David C. Parker -- The Greek Minuscules of the New Testament /Barbara Aland and Klaus Wachtel -- The Greek Lectionaries of the New Testament /Carroll Osburn -- The Diatessaron of Tatian /Ulrich B. Schmid -- The Syriac Versions of the New Testament /Peter J. Williams -- The Latin Version of the New Testament /Philip Burton -- The Coptic Versions of the New Testament /Christian Askeland -- The Ethiopic Version of the New Testament /Rochus Zuurmond and Curt Niccum -- The Armenian Version of the New Testament /S. Peter Cowe -- The Georgian Version of the New Testament /Jeff W. Childers -- The Gothic Version of the New Testament /Carla Falluomini -- The Use of the Greek Fathers for New Testament Textual Criticism /Gordon D. Fee and Roderic L. Mullen -- The Use of the Latin Fathers for New Testament Textual Criticism /H.A.G. Houghton -- The Use of the Syriac Fathers for New Testament Textual Criticism /Sebastian Brock -- Additional Greek Witnesses to the New Testament (Ostraca, Amulets, Inscriptions, and Other Sources) /Peter M. Head -- Scribal Tendencies in the Transmission of the Text of the New Testament /James R. Royse -- The Social History of Early Christian Scribes /Kim Haines-Eitzen -- Analyzing and Categorizing New Testament Greek Manuscripts /Thomas C. Geer Jr. and Jean-François Racine -- Textual Clusters: Their Past and Future in New Testament Textual Criticism /Eldon Jay Epp -- Criteria for Evaluating Readings in New Testament Textual Criticism /Tommy Wasserman -- Conjectural Emendation and the Text of the New Testament /Jan Krans -- From “Original Text” to “Initial Text”: The Traditional Goal of New Testament Textual Criticism in Contemporary Discussion /Michael W. Holmes -- Modern Critical Editions and Apparatuses of the Greek New Testament /Juan Hernández Jr. -- The Majority Text Theory: History, Methods, and Critique /Daniel B. Wallace -- Thoroughgoing Eclecticism in New Testament Textual Criticism /J. Keith Elliott -- Reasoned Eclecticism in New Testament Textual Criticism /Michael W. Holmes -- The Text as Window: New Testament Manuscripts and the Social History of Early Christianity /Bart D. Ehrman -- Index of Bible Manuscripts, Modern Editions, and Apparatuses /Bart D. Ehrman and Michael W. Holmes -- Index of Ancient Names /Bart D. Ehrman and Michael W. Holmes -- Index of Modern Names /Bart D. Ehrman and Michael W. Holmes -- Index of Subjects /Bart D. Ehrman and Michael W. Holmes.